Dynamics of Investment and Firm Performance: Comparative evidence from manufacturing industries - Marco Grazzi; Nadia Jacoby; Tania Treibich (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
If the relation between investment and economic growth is well established in the macroeconomic literature, the existence of a similar link at the level of the firm has been challenged by empirical work. This paper investigates the channels linking investment and firm performance in the French and Italian manufacturing industries. It does so by putting forth a novel methodology to identify investment spikes that corrects for size dependence. While maintaining the desired properties of a spike measure, our chosen proxy retrieves the expected relation between investment and firm performance. Ex-ante, more efficient and fast growing firms display a higher probability to invest; in turn, after an investment spike has taken place the group of investing firms shows further gains in performance. Finally, expansionary investment episodes, as proxied by the opening of new plants, have a negative effect on profitability while they are associated with higher sales and employment levels.
Keywords: C14; D22; D24; D92; E22; L11; L23; L60; 330